Millimeter-Long Silicon Photonic Antenna for Optical Phased Arrays at 2-μm Wavelength Band - Dongliang Li; Yingjie Liu; Qinghai Song; Jiangbing Du; Ke Xu (IEEE Photonics Journal)
Silicon photonic optical phased arrays are promising solutions for solid-state LIDAR. But the nonlinear absorption significantly saturates the optical power in the waveguides at 1.5-μm wavelengths. Besides, the high refractive index contrast of silicon grating exhibits a strong diffraction strength of the antenna, which results in a limited aperture of the device. These ultimately place a limit on the detection accuracy and reach. Here, a shallow etched two-dimensional subwavelength grating structure is proposed to improve the efficiency and aperture of the waveguide antenna. A reduction of diffraction strength is achieved via nanohole structure instead of conventional grating lines. Thus, a millimeter-long optical antenna is demonstrated with a peak efficiency of 71%. The far-field diffracted beam width of 0.035° and vertical field-of-view of 17.5° are achieved within 100 nm wavelengths range from 1.95 μm to 2.05 μm. The operation at 2-μm waveband also guarantees better eye-safety and significantly reduces the nonlinear absorption in silicon waveguide compared with conventional 1.5-μm band.